Exploring the process of adjustment following partner death in younger, widowed individuals: A qualitative systematic review. Issue 5 (28th May 2023) - Anderson, Ellen; Van Vuuren, Julie; Bennett, Kate M.; Soulsby, Laura K.
Abstract: Age influences the experience of widowhood and the likelihood of adverse outcomes. This review synthesizes 13 qualitative studies that explored adjustment following the death of a partner at a younger age, within a Western-cultural context. Thematic synthesis identified six analytical themes: unique challenges; identity changes; levels of distress; coping; support; and adapting following the loss. Bereavement challenges younger widow(er)'s life expectations, identity, and friendships. Social support, faith, and access to age-specific support may facilitate positive adjustment. The findings inform the development of effective interventions to support positive adjustment in younger widowhood.